2013
DOI: 10.1103/physrevlett.110.236803
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Weak and Strong Topological Insulators

Abstract: A global phase diagram of disordered weak and strong topological insulators is established numerically. As expected, the location of the phase boundaries is renormalized by disorder, a feature recognized in the study of the so-called topological Anderson insulator. Here, we report unexpected quantization, i.e., robustness against disorder of the conductance peaks on these phase boundaries. Another highlight of the work is on the emergence of two subregions in the weak topological insulator phase under disorder… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
136
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 29 publications
6
136
1
Order By: Relevance
“…Through a d = 2 + ǫ expansion of the critical properties, it is found that the leading order results for the critical exponents in d = 3 are z = 3/2 and ν = 1, for both potential and axial disorder, while there should be no such transition for mass disorder [8]. Recently, numerical calculations have also come to bear on the problem through the study of a three dimensional disordered topological insulator [13,14], a three-dimensional layered Chern insulator [15], a Weyl semimetal [16][17][18], and the phase diagram of Dirac [19] and Weyl [20] semimetals. For the case of a single Weyl cone which can be realized on the surface of a four dimensional topological insulator, the critical exponents have been numerically obtained to high accuracy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Through a d = 2 + ǫ expansion of the critical properties, it is found that the leading order results for the critical exponents in d = 3 are z = 3/2 and ν = 1, for both potential and axial disorder, while there should be no such transition for mass disorder [8]. Recently, numerical calculations have also come to bear on the problem through the study of a three dimensional disordered topological insulator [13,14], a three-dimensional layered Chern insulator [15], a Weyl semimetal [16][17][18], and the phase diagram of Dirac [19] and Weyl [20] semimetals. For the case of a single Weyl cone which can be realized on the surface of a four dimensional topological insulator, the critical exponents have been numerically obtained to high accuracy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Along a separate vein, the subject of weak topological insulators (WTIs) is also an area of ongoing research activity [27][28][29][30][31] . WTIs are mostly spoken of in the context of three-dimensional (3D) systems 32,33 .…”
mentioning
confidence: 99%
“…The metallic phase, where disorder is a relevant perturbation, is topologically trivial. Recently, there has been a surge of analytical [34][35][36][37][38][39][40][41][42] and numerical [43][44][45][46][47][48][49][50][51][52] works, exploring the effects of disorder in regular Dirac and Weyl semimetals.…”
Section: T ) the Corresponding Hamiltonian Ismentioning
confidence: 99%